Electrolyte composition, battery separator, and battery

CN122953555APending Publication Date: 2026-10-20LG CHEM LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202580020385.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-12-20
Filing Date
2025-12-22
Publication Date
2026-10-20

AI Technical Summary

Benefits of technology

[0051]本发明的电解质组合物可以提高电解质的离子传导性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The electrolyte composition of the present invention comprises a binder, a liquid electrolyte, a crosslinking agent, and a photopolymerization initiator and satisfies at least a specific formula, and the battery separator and battery of the present invention comprise the electrolyte composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This document claims the benefit based on priority of Korean Patent Application No. 10-2024-0193077, filed with the Korean Intellectual Property Office on December 20, 2024, the entire contents of which are incorporated herein by reference.

[0002] This invention relates to an electrolyte composition.

[0003] This invention relates to a battery separator.

[0004] This invention relates to a battery. Background Technology

[0005] Gel polymer electrolytes (GPEs) can contain both a binder and a liquid electrolyte. GPEs are typically incorporated into the electrodes of a battery and can be blended with the electrode active materials. In this case, a polyolefin-based membrane can be positioned between the electrodes (positive and negative) to act as a separator to prevent physical short circuits between the electrodes. Summary of the Invention

[0006] Technical issues

[0007] The binder of a gel polymer electrolyte may have crystalline portions in its structure, which reduces the ionic conductivity of the electrolyte.

[0008] It is difficult to improve the ionic conductivity of gel polymer electrolytes while simultaneously improving battery life and safety.

[0009] Technical solution

[0010] One embodiment of the present invention is an electrolyte composition comprising: a binder, a liquid electrolyte, and a crosslinking agent, and satisfying at least Formula 1 to Formula 3:

[0011] [Formula 1]

[0012] 500 ≤ X ≤ 9000

[0013] [Equation 2]

[0014] 50 ≤ Y < X

[0015] [Formula 3]

[0016] 0 < Y / X ≤ 0.5

[0017] In Equations 1 to 3, X is the storage modulus of the electrolyte composition (Pa, 25°C, 0.1 radians / second), and Y is the loss modulus of the electrolyte composition (Pa, 25°C, 0.1 radians / second).

[0018] The electrolyte composition can also satisfy the following formula 4:

[0019] [Formula 4]

[0020] 100 ≤ Y < X

[0021] In Equation 4, X and Y are defined according to Equations 1 to 3.

[0022] The electrolyte composition can also satisfy the following formula 5:

[0023] [Formula 5]

[0024] 0.5 ≤ (W / Z) / (Y / X) ≤ 3

[0025] In Equation 5, Z is the storage modulus of the electrolyte composition (Pa, 25°C, 100 radians / second), and W is the loss modulus of the electrolyte composition (Pa, 25°C, 100 radians / second). X and Y are defined according to Equations 1 to 3.

[0026] Z (Pa) can be in the range of 1000 to 1500.

[0027] W (Pa) can be in the range of 250 to 500.

[0028] The adhesive comprises a fluorine-based first adhesive, and the first adhesive may comprise a 1-1 unit of vinylidene fluoride and a 1-2 unit of a fluorine-containing alkyl compound.

[0029] The content (by weight%) of the first adhesive unit 1-2 can be in the range of 10 to 50.

[0030] The weight-average molecular weight (10,000 g / mol) of the first binder can be in the range of 15 to 60.

[0031] The adhesive may also contain an acrylic-based second adhesive, and the second adhesive may contain a 2-1 unit of an alkyl (meth)acrylate and a 2-2 unit of a lactone-based compound.

[0032] The glass transition temperature (°C) of the second adhesive can be in the range of 100 to 140.

[0033] The weight-average molecular weight (10,000 g / mol) of the second binder can be in the range of 5 to 20.

[0034] The electrolyte composition may contain a first binder with a weight equal to or greater than that of the second binder.

[0035] Crosslinking agents may include polyfunctional (meth)acrylate compounds.

[0036] Liquid electrolytes may contain non-aqueous solvents, lithium salts, and additives.

[0037] The electrolyte composition may contain a linear carbonate-based compound with a volume greater than that of a cyclic carbonate-based compound.

[0038] Compounds based on linear carbonates may include dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl ethyl carbonate, or combinations thereof.

[0039] Compounds based on linear carbonates can be liquids at room temperature.

[0040] Compounds based on cyclic carbonates may include ethylene carbonate, vinylene carbonate, ethylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, propylene carbonate, butyl carbonate, or combinations thereof.

[0041] Compounds based on cyclic carbonates can be solid at room temperature.

[0042] The volume (volume %) of the linear carbonate-based compound in the electrolyte composition can be in the range of 55 to 95.

[0043] Lithium salts include LiPF6, LiBF4, LiCl, LiBr, LiI, LiClO4, LiAsF6, LiCH3CO2, LiCF3SO3, LiN(CF3SO2)2, LiN(FSO2)2, LiC(CF2SO2)3, or combinations thereof, and additives may include vinylene carbonate, 1,3-propane sulpholactone, 1,3-propene sulpholactone, lithium difluorophosphate, lithium tetrafluoro(oxalate)phosphate, lithium bis(fluorosulfonyl)imide, fluoroethylene carbonate, ethylene ethylene carbonate, or combinations thereof.

[0044] Another embodiment of the present invention is a battery separator, which includes a base layer and an electrolyte layer, the electrolyte layer being positioned on one or both sides of the base layer and containing an electrolyte composition.

[0045] The base layer may include a polyolefin-based membrane.

[0046] The electrolyte layer may contain a cured product of the electrolyte composition.

[0047] The battery separator may also include an inorganic layer located between the substrate layer and the electrolyte layer and containing inorganic particles.

[0048] Inorganic particles may include SrTiO3, SnO2, CeO2, MgO, Mg(OH)2, NiO, CaO, ZnO, Zn2SnO4, ZnSnO3, ZnSn(OH)6, ZrO2, Y2O3, Al2O3, AlOOH, Al(OH)3, TiO2, or combinations thereof.

[0049] Another embodiment of the present invention is a battery comprising: a positive electrode, a negative electrode, and a separator positioned between the positive electrode and the negative electrode, wherein the separator comprises a substrate layer and an electrolyte layer, the electrolyte layer being positioned on one or both sides of the substrate layer and comprising an electrolyte composition.

[0050] Beneficial effects

[0051] The electrolyte composition of the present invention can improve the ionic conductivity of electrolytes.

[0052] The battery separator of the present invention has improved ion conductivity and can simultaneously ensure battery life and safety.

[0053] The battery of the present invention can simultaneously ensure improved performance, lifespan and safety. Attached Figure Description

[0054] Figure 1 The rheological property analysis results of Example 1 are shown.

[0055] Figure 2 The rheological property analysis results of Example 2 are shown.

[0056] Figure 3 The rheological property analysis results of Example 3 are shown.

[0057] Figure 4 The rheological property analysis results of Comparative Example 1 are shown.

[0058] Figure 5 The rheological property analysis results of Comparative Example 2 are shown.

[0059] Figure 6 The results of the rheological property analysis of Comparative Example 3 are shown.

[0060] Figure 7 These are the charge-discharge curves of the batteries of Examples 1 to 3 and Comparative Examples 2 to 3.

[0061] Figure 8 The electrode utilization rate of Examples 1 to 3 and Comparative Example 2 as a function of the number of battery cycles is shown. Detailed Implementation

[0062] This document may use ordinal numbers such as "first" and "second" to refer to multiple components. There is no priority among the components.

[0063] In this document, when a specific commercial product is used as a component, the characteristics of that component may refer to the characteristics described in the product’s Technical Data Sheet (TDS) or Certificate of Analysis (COA).

[0064] In this document, when the physical properties of a particular material vary with temperature and pressure, the measurement standard for that property can be 25°C and 101.325 kPa.

[0065] In this document, the numerical range “within the range of A to B” means “A or greater and B or less”.

[0066] The values ​​mentioned in this document are rounded. For example, 1.5 is a number in the range of 1.45 to 1.54.

[0067] The invention is described in more detail below.

[0068] One embodiment of the present invention is an electrolyte composition. The electrolyte composition may be a composition of gel polymer electrolytes.

[0069] In this document, a gel polymer electrolyte is an electrolyte in a gel phase and comprises a polymer matrix and a liquid electrolyte impregnated therein. Here, the polymer matrix physically supports the gel polymer electrolyte. The liquid electrolyte imparts ionic conductivity to the gel polymer electrolyte.

[0070] In this document, an electrolyte composition refers to a composition that can be transformed into a gel polymer electrolyte by itself or through a predetermined reaction.

[0071] The electrolyte composition comprises a binder, a liquid electrolyte, and a crosslinking agent.

[0072] Binders can form the polymer matrix in gel polymer electrolytes, either alone or together with crosslinking agents. Binders can also serve as mechanical supports for gel polymer electrolytes.

[0073] Liquid electrolytes can be impregnated in a polymer matrix formed by a binder. Liquid electrolytes can impart ionic conductivity to gel polymer electrolytes.

[0074] Crosslinking agents can form the polymer matrix in a gel polymer electrolyte, either alone or together with a binder. Crosslinking agents can connect binders and / or crosslinking agents within the polymer matrix.

[0075] The electrolyte compositions of the present invention satisfy specific rules. Specifically, the electrolyte compositions satisfy at least the following formulas 1 to 3:

[0076] [Formula 1]

[0077] 500 ≤ X ≤ 9000

[0078] [Equation 2]

[0079] 50 ≤ Y < X

[0080] [Formula 3]

[0081] 0 < Y / X ≤ 0.5

[0082] X represents the storage modulus of the electrolyte composition (Pa, 25°C, 0.1 radians / second). That is, Formula 1 indicates that the storage modulus of the electrolyte composition (Pa, 25°C, 0.1 radians / second) is in the range of 500 to 9000. The storage modulus of the electrolyte composition can affect whether the cured product is hard or soft. The higher X is, the harder the electrolyte composition may be. The lower X is, the softer the electrolyte composition may be.

[0083] When X is greater than 9000, only hard properties are imparted to the electrolyte composition, which reduces lithium-ion mobility and increases the electrolyte resistance.

[0084] When X is less than 500, the electrolyte composition is formed in a liquid phase with a high impurity content, which increases the resistance of the electrolyte, or even when formed in a semi-solid phase, the ionic conductivity cannot be sufficiently improved.

[0085] Y is the loss modulus of the electrolyte composition (Pa, 25℃, 0.1 radians / second). That is, Equation 2 means that the loss modulus of the electrolyte composition (Pa, 25℃, 0.1 radians / second) is 50 or greater and less than the storage modulus of the electrolyte composition (Pa, 25℃, 0.1 radians / second).

[0086] When Y is less than 50 or when Y is X or greater, the electrolyte composition exhibits a liquid phase. Liquid-phase electrolyte compositions are prone to evaporation or leakage when external forces are applied.

[0087] Equation 3 means that the loss tangent (the ratio of loss modulus to storage modulus) of the electrolyte composition is greater than 0 and is 5 or less. When the loss tangent is close to 0, the electrolyte composition is close to a solid phase. When the loss tangent is close to 1, the electrolyte composition is close to a liquid phase.

[0088] That is, at least all of the electrolyte compositions of Formulas 1 to 3 have semi-solid electrolyte characteristics and can provide an electrolyte that improves battery safety and lifespan while simultaneously improving ion conductivity to further improve battery electrical performance.

[0089] The rheological properties of the electrolyte composition, such as storage modulus and loss modulus, can be values ​​measured in the electrolyte composition itself or in the cured product obtained by curing the electrolyte composition under predetermined conditions.

[0090] There are various methods to make an electrolyte composition satisfy all of Formulas 1 to 3. For example, an electrolyte composition satisfying all of Formulas 1 to 3 can be prepared by using a binder having a specific composition and / or physical properties as a binder, or by using a solvent, lithium salt, additive or a combination thereof of a specific type and composition as a liquid electrolyte.

[0091] The methods for measuring X and Y are covered in more detail in the Examples section of this document.

[0092] The X and Y of Equation 1 can also be adjusted more specifically.

[0093] Specifically, X (Pa) can be 550 or greater, 580 or greater, 600 or greater, 610 or greater, 620 or greater, 650 or greater, 700 or greater, 800 or greater, 900 or greater, 1000 or greater, 2000 or greater, 3000 or greater, or 4000 or greater. X (Pa) can be 8000 or less, 7000 or less, 6000 or less, 5000 or less, 4000 or less, 3000 or less, 2000 or less, 1000 or less, 900 or less, 800 or less, or 700 or less.

[0094] Y (Pa) can be 60 or greater, 70 or greater, 80 or greater, 90 or greater, 100 or greater, 125 or greater, 130 or greater, 135 or greater, or 140 or greater.

[0095] Y (Pa) can be 450 or less, 400 or less, 350 or less, 300 or less, 250 or less, 200 or less, or 150 or less. This presupposes that Y is less than X.

[0096] Specifically, the electrolyte composition can also satisfy the following formula 4:

[0097] [Formula 4]

[0098] 100 ≤ Y < X

[0099] That is, preferably Y (Pa) is 100 or greater and less than X.

[0100] The electrolyte composition of the present invention can produce an electrolyte whose internal structure can elastically and continuously withstand external deformation. That is, in the electrolyte composition of the present invention, even when the angular velocity measured by rheological properties increases, it may not be observed that the loss tangent increases rapidly. By keeping the rate of change of the loss tangent according to the angular velocity measured by rheological properties within an appropriate range, phenomena such as electrolyte leakage in the battery can be prevented. Specifically, the electrolyte composition of the present invention can also satisfy the following formula 5:

[0101] [Formula 5]

[0102] 0.5 ≤ (W / Z) / (Y / X) ≤ 3

[0103] In Equation 5, Z is the storage modulus of the electrolyte composition (Pa, 25°C, 100 radians / second). W is the loss modulus of the electrolyte composition (Pa, 25°C, 100 radians / second).

[0104] In Equation 5, (W / Z) refers to the loss tangent of the electrolyte composition at an angular velocity of 100 radians / second. That is, the ratio of the loss tangent of the electrolyte composition of the present invention can be adjusted within a specific range before / after the increase of the angular velocity measured by rheological properties.

[0105] Z (Pa) can be in the range of 1000 to 1500. Specifically, Z (Pa) can be 1050 or greater, 1100 or greater, 1150 or greater, 1195 or greater, 1200 or greater, 1250 or greater, 1260 or greater, or 1265 or greater. Z (Pa) can be 1450 or less, 1400 or less, 1350 or less, 1300 or less, 1265 or less, 1260 or less, 1250 or less, 1200 or less, or 1195 or less.

[0106] W (Pa) can be in the range of 250 to 500. W (Pa) can be 260 or greater, 270 or greater, 280 or greater, 290 or greater, 300 or greater, 310 or greater, 320 or greater, 330 or greater, 340 or greater, 345 or greater, 350 or greater, 360 or greater, or 370 or greater. W (Pa) can be 490 or less, 480 or less, 470 or less, 460 or less, 450 or less, 440 or less, 430 or less, 420 or less, 410 or less, 400 or less, 390 or less, 380 or less, or 370 or less.

[0107] The binder can form the framework of the electrolyte layer formed from the electrolyte composition. The binder has suitable crystallinity and polarity, and can improve the ionic conductivity of the battery separator. In particular, the polar portion of the binder can bond with a crosslinking agent. In this case, the binder can form a crosslinked structure in the electrolyte layer.

[0108] The adhesive may include a first adhesive, and the first adhesive may be a fluorine-based adhesive. That is, the adhesive may include a fluorine-based first adhesive. A fluorine-based adhesive may refer to an adhesive whose constituent units contain fluorine in part or all. Fluorine-based adhesives may include PVDF-based adhesives.

[0109] PVDF-based adhesives can be homopolymers or copolymers comprising polymeric units derived from vinylidene fluoride. Fluorine-based adhesives can comprise 1-1 units of vinylidene fluoride and 1-2 units of a fluorinated alkyl vinyl compound. PVDF-based adhesives can be block copolymers or random copolymers comprising 1-1 and 1-2 units. Preferably, PVDF-based adhesives can be random copolymers comprising 1-1 and 1-2 units.

[0110] Fluorinated alkyl vinyl compounds can refer to at least one of them composed of C n H (2n+1-y) F y The indicated compound is a fluorinated alkyl group bonded to a vinyl group. However, vinylidene fluoride is excluded here.

[0111] Fluorinated alkyl vinyl compounds may include at least one selected from vinyl fluoride, trifluoroethylene, tetrafluoroethylene, trifluorochloroethylene, and hexafluoropropylene. Preferably, the fluorinated alkyl vinyl compound may include at least one selected from hexafluoropropylene, tetrafluoroethylene, and trifluorochloroethylene. More preferably, the fluorinated alkyl vinyl compound may include hexafluoropropylene.

[0112] The content of units 1 and 2 of the first binder can be adjusted. The content of units 1 and 2 of the fluorine-based binder may affect the crystallinity of the fluorine-based binder as well as the ionic conductivity and mechanical strength of the composite electrolyte.

[0113] The content (by weight) of the first adhesive's 1-2 units can be in the range of 10 to 50%. Preferably, the content (by weight) of the first adhesive's 1-2 units can be 15 or more, 16 or more, 17 or more, or 18 or more. The content (by weight) of the first adhesive's 1-2 units can be 40 or less, 30 or less, 25 or less, 23 or less, 21 or less, 20 or less, or 19 or less.

[0114] The content of units 1-1 and 1-2 of the first adhesive can be determined by the content of the first adhesive.19 F-NMR analysis was used for measurement.

[0115] The weight-average molecular weight of the first adhesive can also be adjusted. The weight-average molecular weight (10,000 g / mol) of the first adhesive can be in the range of 15 to 60. Preferably, the weight-average molecular weight (10,000 g / mol) of the first adhesive can be 20 or greater, 25 or greater, 30 or greater, or 35 or greater. The weight-average molecular weight (10,000 g / mol) of the first adhesive can be 55 or less, 50 or less, 45 or less, 40 or less, or 35 or less.

[0116] The weight-average molecular weight of the first binder can be measured by gel permeation chromatography.

[0117] The melting point of the first adhesive can also be adjusted. The melting point (°C) of the first adhesive can be in the range of 100 to 140. Preferably, the melting point (°C) of the first adhesive can be 110 or higher or 115 or higher. The melting point (°C) of the first adhesive can be 135 or lower, 130 or lower, or 125 or lower.

[0118] In addition to the first adhesive, the adhesive may also contain a second adhesive. The second adhesive may be an acrylic-based adhesive. That is, the adhesive may also contain an acrylic-based second adhesive.

[0119] Acrylic-based adhesives may include adhesives based on (meth)acrylates, adhesives based on (meth)acrylamide, or combinations thereof.

[0120] In this document, (meth)acryloyl means methacryloyl or acryloyl.

[0121] The second binder can be a copolymer comprising alkyl (meth)acrylate units as a major component. The second binder can comprise 2-1 units of alkyl (meth)acrylate and 2-2 units of a comonomer. The comonomer can include lactone-based compounds. Therefore, the second binder can comprise 2-1 units of alkyl (meth)acrylate and 2-2 units of a lactone-based compound.

[0122] Alkyl methacrylates may include alkyl methacrylates in which the alkyl group has four or more carbon atoms, alkyl methacrylates in which the alkyl group has three or fewer carbon atoms, or combinations thereof.

[0123] Alkyl esters of (meth)acrylate having 4 or more carbon atoms may include n-butyl (meth)acrylate, tert-butyl (meth)acrylate, sec-butyl (meth)acrylate, pentyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 2-ethylbutyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, lauryl (meth)acrylate, tetradecyl (meth)acrylate, or combinations thereof.

[0124] Alkyl esters of (meth)acrylate having 3 or fewer carbon atoms may include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, or combinations thereof.

[0125] Preferably, unit 2-1 can be methyl methacrylate.

[0126] The molecular weight and glass transition temperature of the second binder can be adjusted. The molecular weight and glass transition temperature of the second binder may affect the miscibility of the second binder with the remaining components.

[0127] The glass transition temperature (°C) of the second adhesive can be in the range of 100 to 140. Specifically, the glass transition temperature (°C) of the second adhesive can be 105 or higher, 110 or higher, 115 or higher, 120 or higher, 123 or higher, or 125 or higher. The glass transition temperature (°C) of the second adhesive can be 135 or lower, 130 or lower, 125 or lower, 123 or lower, or 120 or lower.

[0128] The weight-average molecular weight (10,000 g / mol) of the second binder can be in the range of 5 to 20. The weight-average molecular weight (10,000 g / mol) of the second binder can be 6 or greater, 7 or greater, 8 or greater, 9 or greater, 10 or greater, 11 or greater, or 12 or greater. The weight-average molecular weight (10,000 g / mol) of the second binder can be 19 or less, 18 or less, 17 or less, 16 or less, 15 or less, 14 or less, 13 or less, or 12 or less.

[0129] When an adhesive contains both a first adhesive and a second adhesive, their blending ratio can also be adjusted.

[0130] Specifically, the electrolyte composition may contain a first binder with a weight equal to or greater than that of the second binder.

[0131] In the electrolyte composition, the weight ratio (B1:B2) of the first binder to the second binder can be in the range of 5:5 to 9:1. Preferably, the weight ratio (B1:B2) of the first binder to the second binder can be in the range of 5.5:4.5 to 9:1, 6:4 to 9:1, 6.5:3.5 to 9:1, 7:3 to 9:1, 7.5:2.5 to 9:1, 8:2 to 9:1, or 8.5:1.5 to 9:1.

[0132] Crosslinking agents may contain crosslinkable functional groups. These crosslinkable functional groups may be bonded between binders and / or crosslinking agents within a polymer matrix.

[0133] The crosslinkable functional group may include a photoreactive functional group. Specifically, the crosslinkable functional group may include a (meth)acryloyl group as a photoreactive functional group. The crosslinking agent may include a compound based on a polyfunctional (meth)acrylate. Preferably, from the viewpoint of the rate of crosslinking reaction and prevention of degradation of electrochemical properties caused by the rigidity of the polymer network, the crosslinkable functional group may include an acryloyl group as a photoreactive functional group.

[0134] The crosslinking agent can have two or more crosslinkable functional groups. Specifically, the crosslinking agent can have three or more, or four or more crosslinkable functional groups. The crosslinking agent can have six or fewer, five or fewer, or four or fewer crosslinkable functional groups.

[0135] Crosslinking agents may include di(meth)acrylate-based compounds, tri(meth)acrylate-based compounds, tetra(meth)acrylate-based compounds, penta(meth)acrylate-based compounds, hexa(meth)acrylate-based compounds, or combinations thereof.

[0136] Specifically, the crosslinking agent may include di(meth)acrylate-based compounds, tri(meth)acrylate-based compounds, tetra(meth)acrylate-based compounds, penta(meth)acrylate-based compounds, or combinations thereof.

[0137] More specifically, crosslinking agents may include di(meth)acrylate-based compounds, tri(meth)acrylate-based compounds, or combinations thereof.

[0138] More specifically, crosslinking agents may include compounds based on tri(meth)acrylates.

[0139] More specifically, crosslinking agents may include triacrylate-based compounds.

[0140] Crosslinking agents can include monomeric compounds, polymeric compounds, or combinations thereof. A monomeric crosslinking agent can mean a crosslinking agent in which the portion other than the crosslinkable functional groups is derived from a monomer. A polymeric crosslinking agent can mean a crosslinking agent in which the portion other than the crosslinkable functional groups is derived from a polymer.

[0141] Crosslinking agents may include polyethylene glycol di(meth)acrylate, poly(ethylene oxide-propylene oxide) di(meth)acrylate, polyurethane di(meth)acrylate, polycarbonate di(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, glycerol tri(meth)acrylate, ethoxylated glycerol tri(meth)acrylate, propoxylated glycerol tri(meth)acrylate, tri(2-hydroxyethyl)isocyanate, and tris(2-hydroxyethyl)isocyanate. Cyanourea tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, propoxylated pentaerythritol tetra(meth)acrylate, erythritol tetra(meth)acrylate, bis(trimethylolpropane) tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, ethoxylated dipentaerythritol penta(meth)acrylate, sorbitol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ethoxylated dipentaerythritol hexa(meth)acrylate, sorbitol hexa(meth)acrylate, or combinations thereof.

[0142] Specifically, the crosslinking agent may include trimethylolpropane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, glycerol tri(meth)acrylate, ethoxylated glycerol tri(meth)acrylate, propoxylated glycerol tri(meth)acrylate, tri(2-hydroxyethyl)isocyanurate tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ethoxylated tri(meth)acrylate, etc. The methylated pentaerythritol tetra(meth)acrylate, propoxylated pentaerythritol tetra(meth)acrylate, erythritol tetra(meth)acrylate, bis(trimethylolpropane) tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, ethoxylated dipentaerythritol penta(meth)acrylate, sorbitol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ethoxylated dipentaerythritol hexa(meth)acrylate, sorbitol hexa(meth)acrylate, or combinations thereof.

[0143] More specifically, the crosslinking agent may include trimethylolpropane triacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, glycerol triacrylate, ethoxylated glycerol triacrylate, propoxylated glycerol triacrylate, tri(2-hydroxyethyl) isocyanurate triacrylate, pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetraacrylate, propoxylated pentaerythritol tetraacrylate, erythritol tetraacrylate, bis(trimethylolpropane) tetraacrylate, dipentaerythritol pentaacrylate, ethoxylated dipentaerythritol pentaacrylate, sorbitol pentaacrylate, dipentaerythritol hexaacrylate, ethoxylated dipentaerythritol hexaacrylate, sorbitol hexaacrylate, or combinations thereof.

[0144] More specifically, crosslinking agents may include trimethylolpropane triacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, glycerol triacrylate, ethoxylated glycerol triacrylate, propoxylated glycerol triacrylate, tri(2-hydroxyethyl)isocyanurate triacrylate, or combinations thereof.

[0145] The liquid electrolyte can be impregnated in a binder, specifically in a polymer matrix formed by the binder. The liquid electrolyte may also contain a non-aqueous solvent, a lithium salt, and additives. The lithium salt can be dissolved in the non-aqueous solvent.

[0146] Non-aqueous solvents can refer to organic solvents that are free of water or contain trace amounts of water. Non-aqueous solvents can include carbonate-based compounds, ether-based compounds, ester-based compounds, compounds containing polar functional groups, or mixtures thereof. Preferably, non-aqueous solvents can include carbonate-based compounds.

[0147] Ether-based compounds may include dimethoxyethane, diethoxyethane, tetrahydrofuran, or combinations thereof.

[0148] Ester-based compounds may include N-methyl-2-pyrrolidone (NMP), γ-butyrolactone (γ-butyrolactone), or combinations thereof.

[0149] Compounds containing polar functional groups may include dimethyl sulfoxide, acetonitrile, or combinations thereof.

[0150] Carbonate-based compounds may include linear carbonate-based compounds, cyclic carbonate-based compounds, or combinations thereof. Preferably, carbonate-based compounds may include both linear carbonate-based compounds and cyclic carbonate-based compounds.

[0151] In addition, carbonate-based compounds may include carbonate-based compounds that are liquid at room temperature and carbonate-based compounds that are solid at room temperature.

[0152] Electrolyte compositions can contain linear carbonate-based compounds in a larger volume than cyclic carbonate-based compounds. In this case, the miscibility of the binder with the liquid electrolyte increases, and abnormal viscosity increases in the gel polymer electrolyte precursor can be prevented.

[0153] In this document, linear carbonate-based compounds refer to open diesters of carbonic acid. Specifically, linear carbonate-based compounds include structures in which the two hydroxyl groups of carbonic acid are esterified with different alcohols and the entire molecule does not form a ring.

[0154] In this document, cyclic carbonate-based compounds refer to internal esters in which the -O-CO-O- backbone of the carbonate group is contained within a ring structure. Specifically, cyclic carbonate-based compounds include structures in which two hydroxyl groups in a molecule form ester bonds with the same carbonate group at both ends, such that the -O-CO-O- backbone is contained within a ring.

[0155] Compounds based on linear carbonates may include dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl ethyl carbonate, or combinations thereof.

[0156] Specifically, linear carbonate-based compounds may include dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, or combinations thereof.

[0157] More specifically, linear carbonate-based compounds may include ethyl methyl carbonate.

[0158] Compounds based on linear carbonates can be liquids at room temperature.

[0159] Compounds based on cyclic carbonates may include ethylene carbonate, vinylene carbonate, ethylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, propylene carbonate, butyl carbonate, or combinations thereof.

[0160] Specifically, compounds based on cyclic carbonates may include ethylene carbonate, vinylene carbonate, ethylene carbonate, fluoroethylene carbonate, propylene carbonate, butyl carbonate, or combinations thereof.

[0161] More specifically, compounds based on cyclic carbonates may include ethylene carbonate, vinylene carbonate, ethylene carbonate, propylene carbonate, or combinations thereof.

[0162] From the viewpoints of the miscibility of the aforementioned binder and liquid electrolyte, the viscosity adjustment of the electrolyte composition, and the safety of the battery, it is preferable to combine compounds based on linear carbonates and compounds based on cyclic carbonates in a phase-different manner.

[0163] Compounds based on cyclic carbonates can be solid at room temperature. Specifically, compounds based on cyclic carbonates may include ethylene carbonate. The amounts of linear carbonate-based compounds and cyclic carbonate-based compounds used can also be appropriately adjusted within the ranges that satisfy the above conditions.

[0164] The amounts of linear carbonate-based compounds and cyclic carbonate-based compounds used can also be appropriately adjusted within the range that satisfies the above conditions.

[0165] The volume (volume%) of the linear carbonate-based compound in the electrolyte composition can be in the range of 55 to 95.

[0166] Preferably, the volume (volume %) of the linear carbonate-based compound in the electrolyte composition can be 60 or greater, 65 or greater, or 70 or greater. The volume (volume %) of the linear carbonate-based compound in the electrolyte composition can be 90 or less, 85 or less, 80 or less, or 75 or less.

[0167] The volume (volume %) of the cyclic carbonate-based compound in the electrolyte composition can range from 5 to 45. Preferably, the volume (volume %) of the cyclic carbonate-based compound in the electrolyte composition can be 10 or greater, 15 or greater, 20 or greater, or 25 or greater. The volume (volume %) of the cyclic carbonate-based compound in the electrolyte composition can be 40 or less, 35 or less, or 30 or less.

[0168] Lithium salts can refer to materials that decompose into lithium cations and anions upon dissociation.

[0169] Lithium salts may include LiPF6, LiBF4, LiCl, LiBr, LiI, LiClO4, LiAsF6, LiCH3CO2, LiCF3SO3, LiN(CF3SO2)2, LiN(FSO2)2, LiC(CF2SO2)3, or combinations thereof. Preferably, the lithium salt may include LiN(CF3SO2)2.

[0170] Additives can refer to substances that are applied in small amounts to liquid electrolytes for purposes such as stabilizing electrode interfaces, improving electrochemical stability, regulating conductivity, improving temperature characteristics, and suppressing gas generation.

[0171] The additive may include vinylene carbonate, 1,3-propanesulfonyl lactone, 1,3-propenesulfonyl lactone, lithium difluorophosphate, lithium tetrafluoro(oxalate)phosphate, lithium bis(fluorosulfonyl)imide, fluoroethylene carbonate, ethylene ethylene carbonate, or combinations thereof. Preferably, the additive may include vinylene carbonate.

[0172] The electrolyte composition may also contain an initiator.

[0173] An initiator can initiate a reaction in which the binder forms a polymer matrix when a predetermined stimulus is applied.

[0174] The initiator may include a thermal polymerization initiator, a photopolymerization initiator, or a combination thereof. Preferably, the initiator may include a photopolymerization initiator.

[0175] Photopolymerization initiators may include short-wavelength photopolymerization initiators, long-wavelength photopolymerization initiators, or combinations thereof. Preferably, the photopolymerization initiator may include a long-wavelength photopolymerization initiator.

[0176] Short-wavelength photopolymerization initiators may include IRGACURE 127 (1,1'-(methylene-di-4,1-phenylene)bis[2-hydroxy-2-methyl-1-propanone]), IRGACURE 1173 (2-hydroxy-2-methylphenylacetone, HMPP), DMPA (2,2-dimethoxy-2-phenylacetophenone), HOMPP (2-hydroxy-2-methylphenylacetone), LAP (phenyl-2,4,6-trimethylbenzoylphosphonite lithium), or combinations thereof.

[0177] Long-wavelength photopolymerization initiators may include at least one selected from bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide and ethyl (2,4,6-trimethylbenzoyl)phenylphosphine oxide. Preferably, the long-wavelength photopolymerization initiator may include ethyl (2,4,6-trimethylbenzoyl)phenylphosphine oxide (TPO-L).

[0178] Another embodiment of the present invention is a battery separator.

[0179] In this document, a battery may include any device that performs an electrochemical reaction.

[0180] A battery can refer to all types, including primary batteries, secondary batteries, fuel cells, solar cells, and capacitors. A battery can specifically refer to a lithium-ion secondary battery. Lithium-ion secondary batteries can include lithium metal secondary batteries, lithium polymer secondary batteries, lithium-ion polymer secondary batteries, and lithium-ion secondary batteries.

[0181] Battery separators can be positioned between the electrodes in a battery. Specifically, they can be positioned between the positive and negative electrodes. Battery separators prevent physical contact (short circuit) between the positive and negative electrodes. Charge carriers (such as lithium ions) can move between the electrodes through the battery separator.

[0182] The battery separator of the present invention includes a substrate layer and an electrolyte layer.

[0183] The base layer allows fluid to move from one side of the base layer to the other.

[0184] The electrolyte layer is located on one or both sides of the substrate layer. Specifically, the electrolyte layer can be located on the first side of the substrate layer, or on the first side and a second side facing the first side. When the electrolyte layer is located on both the first and second sides, the composition and thickness of each electrolyte layer can be the same or different from each other.

[0185] The electrolyte layer can provide a path for charge carriers to move through the battery separator.

[0186] The electrolyte layer comprises an electrolyte composition according to one embodiment of the present invention. Therefore, the description of the electrolyte composition of the present invention can be applied as is to the description of the battery separator of the present invention.

[0187] Therefore, the battery separator of the present invention has improved ion conductivity and can simultaneously ensure battery life and safety.

[0188] The substrate layer may include a polyolefin-based membrane. Specifically, the substrate layer may include a polyolefin-based porous membrane.

[0189] Here, "polyolefin-based porous membrane" means a porous membrane containing a polyolefin-based resin as the main component.

[0190] Polyolefin-based porous membranes may contain polyolefin-based resin in an amount of 50% or more, 90% or more, or 95% or more of the total material constituting the polyolefin-based porous membrane.

[0191] The weight-average molecular weight of the components contained in polyolefin-based resins can be 3 × 10⁻⁶. 5 Up to 15×10 6 When the weight-average molecular weight of the components contained in a polyolefin-based resin is 1,000,000 or greater, the strength of the separator, including a polyolefin porous membrane, can be improved.

[0192] Polyolefin-based resins may include thermoplastic resins. Thermoplastic resins may include homopolymers (e.g., polyethylene, polypropylene, polybutene) or copolymers (e.g., ethylene-propylene copolymers) formed by polymerizing monomers such as ethylene, propylene, 1-butene, 4-methyl-1-pentene, and 1-hexene.

[0193] Polyolefin-based porous membranes can be layers containing only one of these polyolefin-based resins, or layers containing two or more of these polyolefin-based resins. Polyethylene and high-molecular-weight polyethylene with ethylene as the main chain can block (shut down) the flow of overcurrent at lower temperatures. Furthermore, polyolefin-based porous membranes can also contain components other than polyolefin-based resins that do not impair the membrane's function.

[0194] An electrolyte layer can be formed by curing an electrolyte composition. The electrolyte layer may contain a cured product of the electrolyte composition.

[0195] Curing methods may include, for example, thermal curing, photocuring, and thermal-photocuring. Preferably, the curing method is photocuring.

[0196] The cured product of a composition can refer to a product that has undergone a chemical process in which the composition hardens or solidifies because the structure of the components contained in the composition changes due to chemical reactions between the components. Curing can be different from drying, which is a physical process in which a portion of the composition dries or hardens as some of the components contained in the composition (e.g., solvents such as water, volatile components) evaporate.

[0197] Battery separators may also contain inorganic particles.

[0198] Inorganic particles can exist as a separate layer between the base layer and the electrolyte layer in a battery separator.

[0199] The battery separator may also include an inorganic layer positioned between the substrate layer and the electrolyte layer. In this case, the inorganic particles can be positioned within the inorganic layer.

[0200] Inorganic particles may possess one or more of the following properties: lithium-ion transfer capability, piezoelectricity, and flame retardancy. Preferably, the inorganic particles may be flame-retardant inorganic particles.

[0201] Inorganic particles that transfer lithium ions can contain lithium but do not store it, and exhibit the function of facilitating lithium ion movement. These particles may contain internal defects that can be utilized to allow charge carriers such as lithium ions to move. Therefore, inorganic particles that transfer lithium ions can improve the lithium-ion conductivity within the battery, thereby improving battery performance.

[0202] Inorganic particles that transfer lithium ions may include Lix Ti y (PO4)3(0 <x<2,0<y<3)、Li x Al y Ti z (PO4)3(0 <x<2,0<y<1,0<z<3)、Li x La y TiO3 (0 <x<2,0<y<3)、Li 6+x La3Zr 2-y M y O 12-z (0≤x≤1, 0≤y≤0.5, 0≤z≤0.2), or combinations thereof.

[0203] Piezoelectric inorganic particles are materials that exhibit different electrical conductivities depending on the applied pressure. Specifically, piezoelectric inorganic particles are insulators at atmospheric pressure, but become conductors when a certain pressure is applied. Piezoelectric inorganic particles have a relatively high dielectric constant, which can be 100 or greater. When piezoelectric inorganic particles are stretched or compressed under pressure, they can generate an electric charge. One side of the piezoelectric inorganic particle is positively charged, and the other side is negatively charged, allowing a potential difference to occur within the particle. When a short circuit occurs inside the positive and negative electrodes due to an external impact, the piezoelectric inorganic particles placed in the separator can prevent physical contact between the positive and negative electrodes. This potential difference allows a microcurrent to be applied between the positive and negative electrodes. When a short circuit occurs in the battery, this microcurrent can gradually reduce the battery voltage, thereby improving battery safety.

[0204] Piezoelectric inorganic particles may include those selected from BaTiO3, BaSO4, Pb(Zr,Ti)O3 (PZT), and Pb 1-x La x Zr 1-y Ti y O3 (PLZT) (0) <x<1,0<y<1)、Pb(Mg 1 / 3 Nb 2 / 3 At least one of O3-PbTiO3 (PMN-PT) and HfO2 (hafnium dioxide).

[0205] Flame-retardant inorganic particles can impart flame-retardant properties to the separator and prevent the battery's internal temperature from rising rapidly.

[0206] Flame-retardant inorganic particles may include at least one selected from SrTiO3, SnO2, CeO2, MgO, Mg(OH)2, NiO, CaO, ZnO, Zn2SnO4, ZnSnO3, ZnSn(OH)6, ZrO2, Y2O3, Al2O3, AlOOH, Al(OH)3 and TiO2.

[0207] The content of inorganic particles in the inorganic layer can be 80% by weight or more. The content (by weight) of inorganic particles in the inorganic layer can be in the range of 85 to 99, 85 to 98, 85 to 97, 85 to 96, 85 to 95, 90 to 98, 90 to 97, 90 to 96 or 90 to 95.

[0208] Another embodiment of the present invention is a battery.

[0209] A battery may include a first electrode, a second electrode, a separator, and an electrolyte. The separator may be disposed between the first electrode and the second electrode. The polarity of the first electrode may be opposite to that of the second electrode. If the first electrode is a positive electrode (negative electrode), then the second electrode may be a negative electrode (positive electrode).

[0210] The system formed by the battery separator and the electrolyte can be the battery separator of the present invention. Therefore, in the description of the battery, the description of the separator and the electrolyte can be completely replaced by the aforementioned electrolyte composition and battery separator. Therefore, the battery of the present invention can simultaneously ensure improved performance, lifespan, and safety.

[0211] The positive electrode can be the electrode that carries out the reduction reaction during discharge. The negative electrode can be the electrode that carries out the oxidation reaction during discharge.

[0212] The electrodes of the battery may include electrode active materials attached to the electrode current collector. Specifically, the electrodes may include an electrode current collector and an electrode active material layer disposed on one or both sides of the electrode current collector and containing electrode active materials.

[0213] In the electrode active material, the positive electrode active material may include a lithium intercalation material. The lithium intercalation material may include lithium transition metal oxides. The lithium intercalation material may include lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, lithium iron oxide, lithium nickel manganese oxide, lithium nickel cobalt oxide, lithium nickel manganese cobalt oxide, or combinations thereof. Preferably, the positive electrode active material may include lithium nickel manganese cobalt oxide.

[0214] In electrode active materials, the negative electrode active material may include a lithium intercalation material. The lithium intercalation material may include: lithium-based metals, including lithium metal and lithium alloys; carbon-based compounds, including carbon, petroleum coke, activated carbon, and graphite; or combinations thereof. Preferably, the negative electrode active material may include a carbon-based compound.

[0215] The positive electrode current collector can be a foil of a metal including aluminum, nickel, or a combination thereof. Preferably, the positive electrode current collector can be an aluminum foil.

[0216] The negative electrode current collector can be a foil of a metal including copper, gold, nickel, or a combination thereof. Preferably, the negative electrode current collector can be a copper foil.

[0217] Invention Embodiments

[0218] In the following document, the invention is described in more detail with reference to embodiments and comparative examples. However, this document is not intended to limit the invention to the embodiments.

[0219] [Preparation Example]

[0220] Example 1. Electrolyte composition and battery separator

[0221] (1) A solution was prepared by adding 0.24 g of binder and 0.24 g of crosslinker to 9.5 g of liquid electrolyte, and after stirring the solution with a homogenizer, 0.02 g of photopolymerization initiator was added to the solution to prepare an electrolyte composition. The binder was Kynar 2501-20 from Arkema (polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP); weight average molecular weight: 350,000 g / mol; HFP substitution rate: 18.6% by weight). The crosslinker was M300 from Miwon Specialty Chemical (trimethylolpropane triacrylate). The photopolymerization initiator was Irgacure 127. The liquid electrolyte was an electrolyte in which 1 M LiN(CF3SO2)2 was dissolved in a non-aqueous solvent obtained by mixing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 3:7, and 2% by weight of vinylene carbonate (VC) was added thereto.

[0222] (2) The electrolyte composition is coated on both sides of the substrate layer, wherein the total coating thickness is 60 μm, and UV cured to prepare a battery separator in which the electrolyte layer is positioned on both sides of the substrate layer. The substrate layer is Senior SW309H (a polyolefin film with a thickness of 8.5 μm).

[0223] Example 2. Electrolyte composition and battery separator

[0224] The electrolyte composition and battery separator were prepared by repeating the same steps as in Example 1, except that in (1), the binder was changed to a mixture of 0.168 g of a first binder and 0.072 g of a second binder. The first binder was Kynar 2501-20 from Arkema (polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP); weight-average molecular weight: 350,000 g / mol; HFP substitution rate: 18.6 wt%). The second binder was RX-422 from Nippon Shokubai (methyl methacrylate-lactone copolymer; weight-average molecular weight: 160,000 g / mol; glass transition temperature: 123 °C).

[0225] Example 3. Electrolyte composition and battery separator

[0226] The electrolyte composition and battery separator were prepared by repeating the same steps as in Example 1, except that in (1), the binder was changed to a mixture of 0.12 g of a first binder and 0.12 g of a second binder. The first binder was Kynar 2501-20 from Arkema (polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP); weight-average molecular weight: 350,000 g / mol; HFP substitution rate: 18.6 wt%). The second binder was RX-422 from Nippon Shokubai (methyl methacrylate-lactone copolymer; weight-average molecular weight: 160,000 g / mol; glass transition temperature: 123 °C).

[0227] Comparative Example 1. Electrolyte Composition and Battery Separator

[0228] The electrolyte composition and battery separator were prepared by repeating the same steps as in Example 1, except that in (1), the binder was changed to PEO-4 of Sumitomo Seika (polyethylene oxide; viscosity-average molecular weight: 1,100,000 g / mol to 1,500,000 g / mol).

[0229] Comparative Example 2. Electrolyte Composition and Battery Separator

[0230] The electrolyte composition and battery separator were prepared by repeating the same steps as in Example 1, except that in (1), the binder was changed to Nippon Shokubai's RX-422 (methyl methacrylate-lactone copolymer; weight average molecular weight: 160,000 g / mol; glass transition temperature: 123 °C).

[0231] Comparative Example 3. Electrolyte Composition and Battery Separator

[0232] The electrolyte composition and battery separator were prepared by repeating the same steps as in Example 1, except that in (1), the binder was changed to a mixture of 0.072 g of a first binder and 0.168 g of a second binder. The first binder was Kynar 2501-20 from Arkema (polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP); weight-average molecular weight: 350,000 g / mol; HFP substitution rate: 18.6 wt%). The second binder was RX-422 from Nippon Shokubai (methyl methacrylate-lactone copolymer; weight-average molecular weight: 160,000 g / mol; glass transition temperature: 123 °C).

[0233] [Evaluate]

[0234] Experimental Example 1. Rheological Properties

[0235] The rheological properties of the electrolyte composition were measured according to the following procedure.

[0236] (1) Use the product on the day of manufacture or the day after manufacture as an electrolyte composition sample.

[0237] (2) 10 g of the electrolyte composition sample was placed into an aluminum foil tray with a diameter of 50 mm, and then UV cured to prepare the measurement sample. The curing conditions were as follows:

[0238] Curing machine: LH6

[0239] Light source: H bulb,

[0240] Light source power: 70%,

[0241] Sample passing speed through the curing machine: 4 meters / minute

[0242] Sample-lamp distance: 58 mm

[0243] Lamp preheating time: 1 minute after turning on the lamp power.

[0244] Whether to adjust the irradiation dose based on the lamp's usage history: Before use, place the UV Puck in the UV irradiator to check if the irradiation dose in Table 1 below has been obtained.

[0245] [Table 1]

[0246]

[0247] (3) The rheological properties of the sample were measured by changing the measuring angular velocity using a rheological analyzer (TA Instruments HR-10). The detailed measurement conditions are as follows:

[0248] TA Geometry: 511400.945

[0249] Geometric diameter: 40 mm

[0250] Gap settings: Measurement gap (1000 μm), trimming gap (50 μm, 1000 x 5%)

[0251] Temperature stabilization time: 3 minutes

[0252] Angular velocity scan conditions: 0.1 radians / second to 100 radians / second

[0253] Number of measurements: 1

[0254] Experimental Example 2. Electrical Resistance and Ionic Conductivity

[0255] The resistance and ion conductivity of the battery separator are evaluated according to the following procedure.

[0256] (1) A coin cell with the battery separator positioned between SUS plates, as in the examples and comparative examples, was prepared. The coin cell was a 2016 type, and the area of ​​the battery separator was 2.83 cm². 2 (19 pi).

[0257] (2) The resistance and ionic conductivity of the coin cell were calculated using resistance measurements by electrochemical impedance spectroscopy (EIS) and conversions using the Nyquist plot method. The resistance measurements were performed under AC voltage conditions with an amplitude of 10 mV and a frequency of 1,000,000 Hz to 1,000 Hz.

[0258] Experimental Example 3. Battery Performance

[0259] The performance of batteries made with battery separators is measured according to the following procedure.

[0260] (1) Stamp the battery separator to a size of 32 mm × 44 mm.

[0261] (2) Positive electrode

[0262] 1) A slurry is prepared by uniformly dispersing the following mixture in NMP: 94 wt% of LiNiCoMnO2 (Ni:Co:Mn=6:2:2) as the positive electrode active material, 3 wt% of conductive carbon black (Super P; IMERYS Graphite & Carbon) as the conductive material, and 3 wt% of polyvinylidene fluoride with a weight average molecular weight of about 800,000 as a binder.

[0263] 2) The slurry was prepared at a concentration of 4.0 mAh / cm³. 2 The loading is applied to one side of an aluminum current collector with a thickness of 20 μm, and then dried and rolled to prepare a positive electrode plate in which a layer of positive electrode active material is laminated.

[0264] 3) The positive electrode plate is stamped to 1.54 cm. 2 The size is (14 pi).

[0265] (3) Negative electrode

[0266] 1) A lithium metal (negative electrode active material layer) with a thickness of 10 μm is rolled onto a copper plate with a thickness of 10 μm to prepare a negative electrode plate with a total thickness of 20 μm.

[0267] 2) The negative electrode plate is stamped to 1.76 cm. 2 The size is (15 pi).

[0268] (4) Components

[0269] 1) Fabrication of an electrode assembly having the following structure: wherein the positive active material layer of the positive electrode plate and the negative active material layer of the negative electrode plate are arranged facing each other, and a section cut to 2.83 cm is disposed between the positive and negative active material layers. 2 Battery separator with dimensions of (19 pi).

[0270] 2) The electrode assembly is housed in a bag to complete the battery.

[0271] (5) Measurement

[0272] 1) Prepare an electrochemical analysis apparatus (Toyo, Toscat-3100).

[0273] 2) Charge the battery in CC-CV mode at 0.1 C, 4.2 V, and cutoff 0.05 C, and discharge the battery in CC mode at 0.1 C, 3.0 V.

[0274] [Results and Discussion]

[0275] Figures 1 to 6 The rheological property analysis results of Examples 1 to 3 and Comparative Examples 1 to 3 are shown. Table 2 below summarizes the storage modulus and loss modulus of Examples 1 to 3 and Comparative Examples 1 to 3 based on the main angular velocity.

[0276] [Table 2]

[0277]

[0278] Referring to Table 2, the change in angular velocity measured based on rheological properties (0.1 radians / second → 100 radians / second) was determined, and the loss tangent of Comparative Example 1 increased by more than 3 times. This indicates that the electrolyte composition of Comparative Example 1 has a potential leakage problem during storage.

[0279] Tables 3 and 4 below summarize the performance evaluation results of the battery separators and batteries of Examples 1 to 3 and Comparative Examples 2 to 3.

[0280] [Table 3]

[0281]

[0282] [Table 4]

[0283]

[0284] Figure 7 These are the charge-discharge curves of the batteries of Examples 1 to 3 and Comparative Examples 2 to 3. Figure 8The electrode utilization rate of Examples 1 to 3 and Comparative Example 2 as a function of battery cycle number is shown. (Refer to...) Figure 7 and Figure 8 It was determined that Example 2 was superior in terms of coulombic efficiency and lifespan, while the battery of Comparative Example 3 stopped operating during the initial operation due to severe overvoltage.

Claims

1. An electrolyte composition comprising: a binder, a liquid electrolyte, and a crosslinking agent. And at least satisfy the following equations 1 to 3: [Formula 1] 500 ≤ X ≤ 9000 [Equation 2] 50 ≤ Y < X [Formula 3] 0 < Y / X ≤ 0.5 In equations 1 to 3, X is the storage modulus of the electrolyte composition (Pa, 25°C, 0.1 radians / second), and Y is the loss modulus of the electrolyte composition (Pa, 25°C, 0.1 radians / second).

2. The electrolyte composition according to claim 1, The electrolyte composition also satisfies the following formula 4: [Formula 4] 100 ≤ Y < X In Equation 4, X and Y are defined according to Equations 1 to 3.

3. The electrolyte composition according to claim 1, The electrolyte composition also satisfies the following formula 5: [Formula 5] 0.5 ≤ (W / Z) / (Y / X) ≤ 3 In Equation 5, Z is the storage modulus of the electrolyte composition (Pa, 25°C, 100 radians / second), and W is the loss modulus of the electrolyte composition (Pa, 25°C, 100 radians / second). X and Y are defined according to Equations 1 to 3.

4. The electrolyte composition according to claim 3, Z (Pa) is in the range of 1000 to 1500.

5. The electrolyte composition according to claim 3, W (Pa) is in the range of 250 to 500.

6. The electrolyte composition according to claim 1, The adhesive comprises a fluorine-based first adhesive, and The first adhesive comprises a 1-1 unit of vinylidene fluoride and a 1-2 unit of a fluorinated alkyl compound.

7. The electrolyte composition according to claim 6, The content (by weight%) of the first adhesive of units 1-2 is in the range of 10 to 50.

8. The electrolyte composition according to claim 6, The weight-average molecular weight (10,000 g / mol) of the first adhesive is in the range of 15 to 60.

9. The electrolyte composition according to claim 6, The adhesive further comprises an acrylic-based second adhesive, and The second adhesive comprises a 2-1 unit of an alkyl (meth)acrylate and a 2-2 unit of a lactone-based compound.

10. The electrolyte composition according to claim 9, The glass transition temperature (°C) of the second adhesive is in the range of 100 to 140.

11. The electrolyte composition according to claim 9, The weight-average molecular weight (10,000 g / mol) of the second binder is in the range of 5 to 20.

12. The electrolyte composition according to claim 9, The electrolyte composition comprises the first adhesive in an amount equal to or greater than the weight of the second adhesive.

13. The electrolyte composition according to claim 1, The crosslinking agent mentioned above includes a polyfunctional (meth)acrylate compound.

14. The electrolyte composition according to claim 1, The liquid electrolyte contains a non-aqueous solvent, a lithium salt, and additives.

15. The electrolyte composition according to claim 1, The electrolyte composition comprises a linear carbonate-based compound with a volume greater than that of a cyclic carbonate-based compound.

16. The electrolyte composition according to claim 15, The linear carbonate-based compounds mentioned above include dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl ethyl carbonate, or combinations thereof.

17. The electrolyte composition according to claim 15, The linear carbonate-based compound is a liquid at room temperature.

18. The electrolyte composition according to claim 15, The cyclic carbonate-based compounds mentioned above include ethylene carbonate, vinylene carbonate, ethylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, propylene carbonate, butyl carbonate, or combinations thereof.

19. The electrolyte composition according to claim 15, The cyclic carbonate-based compound is a solid at room temperature.

20. The electrolyte composition according to claim 15, The volume (volume %) of the linear carbonate-based compound in the electrolyte composition is in the range of 55 to 95.

21. The electrolyte composition according to claim 14, The lithium salts mentioned above include LiPF6, LiBF4, LiCl, LiBr, LiI, LiClO4, LiAsF6, LiCH3CO2, LiCF3SO3, LiN(CF3SO2)2, LiN(FSO2)2, LiC(CF2SO2)3, or combinations thereof, and The additives mentioned therein include vinylene carbonate, 1,3-propanesulfonyl lactone, 1,3-propenesulfonyl lactone, lithium difluorophosphate, lithium tetrafluoro(oxalate)phosphate, lithium bis(fluorosulfonyl)imide, fluoroethylene carbonate, ethylene ethylene carbonate, or combinations thereof.

22. A battery separator, comprising: basal layer; and An electrolyte layer, wherein the electrolyte layer is positioned on one or both sides of the substrate layer and comprises the electrolyte composition according to claim 1.

23. The battery separator according to claim 22, The substrate layer comprises a polyolefin-based membrane.

24. The battery separator according to claim 22, The electrolyte layer comprises a cured product of the electrolyte composition.

25. The battery separator according to claim 22, The battery separator further includes an inorganic layer located between the substrate layer and the electrolyte layer and containing inorganic particles.

26. The battery separator according to claim 25, The inorganic particles mentioned therein include SrTiO3, SnO2, CeO2, MgO, Mg(OH)2, NiO, CaO, ZnO, Zn2SnO4, ZnSnO3, ZnSn(OH)6, ZrO2, Y2O3, Al2O3, AlOOH, Al(OH)3, TiO2, or combinations thereof.

27. A battery, comprising: Positive electrode, negative electrode, and a separator positioned between the positive electrode and the negative electrode. The separator comprises a base layer and an electrolyte layer, the electrolyte layer being positioned on one or both sides of the base layer and containing the electrolyte composition according to claim 1.